Nanotechnology-Enhanced Detection of Illicit Drugs: Development of Nano Sensors for Rapid Identification in Liquid Media - Chauhan, Nandini; Sankhla, Mahipal Singh; Sharma, Anuj; Sable, Harsh; Sharma, Tina (Journal of the Electrochemical Society, 2025)
An increasing prevalence of illicit drugs, mainly date rape substances such as alprazolam, ketamine, GHB, LSD, and diazepam presents a growing threat to general safety. Rapid and accurate portable detection technologies are thus much desired for effective monitoring and intervention. This review presents the latest updates on nanosensor detection platforms for the determination of these substances in several liquid media, including water, alcoholic beverages, and soft drinks. The employment of different advanced nanomaterials, gold nanoparticles, carbon nanotubes, and quantum dots, has greatly enhanced signal transduction, sensitivity, and selectivity of various sensing mechanisms, such as electrochemical, surface plasmon resonance, and fluorescence-based methods. A bibliometric study mapping worldwide trends in the subject field, key contributing areas, and publication outlets is given as an aid to the technical backdrop. Altogether, this intertwining view situates the development of science and simultaneously highlights emerging fields of interest and interdisciplinary couplings. Concerning the drawbacks of conventional methods, the review forwards a multipath sensing approach that makes use of synergistic properties of nanomaterials to engineer sensitive, inexpensive, and field-deployable detection devices. The presented outcomes stress the utmost importance of nanotechnology for future applications in drug detection, whose implications are on.